Academic Preparation of a Nurse Practitioner: Doctor of Nursing Practice versus Master of Science in Nursing - Howard, Sydney (My University, 2021)
The Doctor of Nursing Practice (DNP) degree was declared by the American Association of Colleges of Nursing to be the most qualified degree for advanced practice registered nurses (APRN) to enter clinical practice. Despite this recommendation, only 25 percent of schools nationwide have made this transition in their programs due to various barriers posed by programs, including financial constraints, sustainability of the program, and limits on faculty for project implementation. The purpose of this DNP project is to evaluate the differences and similarities between MSN and DNP educational programs in students’ preparation for APRN practice and to document gaps in findings. A readiness assessment tool was utilized to identify readiness to practice and program changes for APRN programs. Of the 92 survey responses, 51 responses met the inclusion and exclusion criteria. Only one DNP-prepared nurse practitioner felt overly-prepared when transitioning to practice. Five MSN-prepared nurse practitioners felt their degree did not meet master’s degree Essentials and were all educated exclusively online or hybrid mostly online. The project’s barriers included small sample size, lack of a standardized tool, and nonresponse bias. Based on these findings of this brief, piloted study, the responses suggest increased preparedness of a doctorally prepared NP compared to a masters prepared NP. There are many opportunities for further investigation to warrant possible recommendation of a standardized education degree for NP preparation.
Keywords: academic preparation, masters-prepared NP, doctorally-prepared NP, NP perception, provider readiness to practice